A Multivariate Pattern Recognition Study of Risk-Factors Indicating Postoperative Thromboembolism Despite Low-Dose Heparin in Major Abdominal Surgery - Kjærgaard, J; Esbensen, K; Wille-Jørgensen, P; Jørgensen, T; Thorup, J; Berning, H; Wold, S (Thrombosis and Haemostasis, 1985)
The object of the present investigation was to identify those who, among high-risk patients, would “break through” low-dose heparin prophylaxis and develop thromboembolism after major abdominal surgery.Twenty-nine variables (clinical characteristics, pre- and postoperative coagulation and fibrinolytic factors) from 19 patients with and 26 patients without thromboembolism were analyzed by means of a multivariate supervised pattern recognition technique (SIMCA).We found no statistically significant difference between patients with and without thromboembolism. Thus, in the studied group of high-risk patients it was not possible to identify a predictive index for selection of individual patients liable to develop postoperative thromboembolism despite low-dose heparin prophylaxis in major abdominal surgery.
Keywords: Heparin prophylaxis; Major abdominal surgery; Risk factors; Multivariate analysis